ANALISIS KARAKTER PADA KARAKTER UTAMA ANIME DEMON SLAYER: KIMETSU NO YAIBA - Illona Zamia Lusaka; Evelyne Henny Lukitasari; Yudi Wibowo (Canthing, 2024)
Anime Demon Slayer: Kimetsu No Yaiba is a 2-dimensional animated series from Japan known as anime. This anime has 4 main characters, namely Kamado Tanjiro, Kamado Nezuko, Agatsuma Zenitsu, and Hashibira Inosuke who are members of the Demon Slayer squad. The research aims to determine the visual elements and meaning of the main characters of the Demon Slayer anime. The meaning of each main character is analyzed and described using design elements and the semiotic perspective of denotation and connotation using Roland Barthes' theory. This research used qualitative research methods with a descriptive approach. Data collection techniques implemented literature study and observation. The results show that everything in the character has its own meaning and function. It is also the characteristic of each character that makes them stand out. The characters' colors also describe each character's personality and special features. The characters Tanjiro, Nezuko, Zenitsu, and Inosuke are easy to remember with their unique characteristics. It means that the mangaka succeeded in creating the main character. Keywords: Roland Barthes Semiotics, Anime, Demon Slayer: Kimetsu No Yaiba, Japan